2018
DOI: 10.1371/journal.pone.0201715
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of the standard genetic code according to three codon positions using an evolutionary algorithm

Abstract: Many biological systems are typically examined from the point of view of adaptation to certain conditions or requirements. One such system is the standard genetic code (SGC), which generally minimizes the cost of amino acid replacements resulting from mutations or mistranslations. However, no full consensus has been reached on the factors that caused the evolution of this feature. One of the hypotheses suggests that code optimality was directly selected as an advantage to preserve information about encoded pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 75 publications
(83 reference statements)
2
30
0
Order By: Relevance
“…In terms of minimization of amino acid replacements resulting from point mutations in codons, measured here by the average conductance, the SGC is placed between the M 1 codes, characterized by the lowest conductance, and the codes from the M 2 and M 3 models. In agreement with our simulation study, other analyses also showed that the SGC is not perfectly optimized in this respect and better codes can be found [11,44,50,57,58,[87][88][89]. Therefore, it is possible that the assignments of amino acids to codons occurred in accordance with other mechanisms, while the minimization of mutation errors was adjusted by the direct optimization of the mutational pressure around the established genetic code [90][91][92][93][94].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of minimization of amino acid replacements resulting from point mutations in codons, measured here by the average conductance, the SGC is placed between the M 1 codes, characterized by the lowest conductance, and the codes from the M 2 and M 3 models. In agreement with our simulation study, other analyses also showed that the SGC is not perfectly optimized in this respect and better codes can be found [11,44,50,57,58,[87][88][89]. Therefore, it is possible that the assignments of amino acids to codons occurred in accordance with other mechanisms, while the minimization of mutation errors was adjusted by the direct optimization of the mutational pressure around the established genetic code [90][91][92][93][94].…”
Section: Discussionsupporting
confidence: 88%
“…This assumption follows the adaptation hypothesis, which claims that the SGC evolved to minimize harmful consequences of mutations or mistranslations of coded proteins [Woese, 1965, Sonneborn, 1965, Epstein, 1966, Goldberg and Wittes, 1966, Haig and Hurst, 1991, Freeland and Hurst, 1998, Freeland et al, 2000, Gilis et al, 2001. Although this code did not turn out perfectly optimized in this respect [B lażej et al, 2018a, B lażej et al, 2016, Massey, 2008, Novozhilov et al, 2007, Santos et al, 2011, Santos and Monteagudo, 2017, B lażej et al, 2018b, B lażej et al, 2019b, Wnetrzak et al, 2019, it shows a general tendency to error minimization in the global scale. This property is better exhibited by its alternative versions [B lażej et al, 2018c, B lażej et al, 2019a], which occurred later in the evolution.…”
Section: Resultsmentioning
confidence: 83%
“…A non-synonymous change may occur in a coding sequence that is most likely due to the mutation at second codon position as the site is the most functionally constrained. Subsequently, the course of evolution will occur at the protein level and its variation is constrained by functional selection (Błażej, Wnętrzak, Mackiewicz, & Mackiewicz, 2018). In fact, the third codon position which regards as synonymous codon site and the least functionally constrained may be in fourfold degenerate via a certain combination of the nucleotide at first and second codon positions (Wald, Alroy, Botzman, & Margalit, 2012).…”
Section: Discussionmentioning
confidence: 99%